Circular Health: exploiting the SDG roadmap to fight AMR - Mantegazza, Luca; De Pascali, Alessandra Mistral; Munoz, Olga; Manes, Costanza; Scagliarini, Alessandra; Capua, Ilaria (Frontiers in Cellular and Infection Microbiology, 2023)
Circular Health is a novel approach to address complex health issues that is based on the expansion of the One Health Paradigm. Circular health recognizes the need for a multidisciplinary convergence effort to complement the biomedical dimension of health. Antimicrobial resistance (AMR) is one of the greatest global concerns for public health that is likely on the rise, given the extensive use of antibiotics during the early Covid-19 years. Prior to the Covid-19 pandemic, an expert group chaired by Jim O’Neill published “The Review on Antimicrobial Resistance”, which contains a final report and recommendations on how to tackle AMR. The report, for the first time, considers AMR from a multi-perspective viewpoint highlighting how it cannot be successfully addressed unless there is a converging approach encompassing many dimensions of the problem. In this perspective, we propose to include the recommendations from that seminal report and other more recent reviews which include the lessons learnt from the Covid-19 pandemic, into the operational framework of the sustainable development goals (SDGs). AMR represents a perfect case study to explore how the SDG roadmap has the potential of becoming the driving force and implementation tool to address complex health issues by pursuing the optimization of resources and actions via a convergent and multi-stakeholder approach. The implementation of health-related policies through the whole spectrum of the SDGs could be both a novel and a well-established framework to inform multi-dimensional policies for more sustainable health in the future.